Strategi Pemasaran Produk Tempe Melelui Digital Marketing - Hutagaol, Julianti Br Hutagaol; Zoniarti, Zoniarti; Simarmata, Sulastri; Rahmanda, Via Nabila; Ramadhan, Sahrul (Jurnal Kewirausahaan & Inovasi, 2025)
Industry is a central point to help and prosper the economy society to always exist and survive with all existing conditions. Because the industry is a planned effort to realize marketing strategies and marketing processes so that this industry continues to run and exist in its marketing. Likewise with the tempe industry in the Mampang Prapatan area, in its operational activities the obstacle faced by tempe industry players is access to marketing, therefore a marketing strategy is needed or efforts to market and introduce a product or service to the community, using a plan and mature tactics, that way, the number of sales can increase. In marketing, a brand or brand is needed that functions to build an image of the product or place of business. By using offline and online promotion methods. The purpose of this Community Service activity is expected to be tempe industry players able to increase sales in order to achieve economic prosperity in the village. Industry is a central point to help and prosper the economy society to always exist and survive with all existing conditions. Because the industry is a planned effort to realize marketing strategies and marketing processes so that this industry continues to run and exist in its marketing. Likewise with the tempe industry in the Mampang Prapatan area, in its operational activities the obstacle faced by tempe industry players is access to marketing, therefore a marketing strategy is needed or efforts to market and introduce a product or service to the community, using a plan and mature tactics, that way, the number of sales can increase. In marketing, a brand or brand is needed that functions to build an image of the product or place of business. By using offline and online promotion methods. The purpose of this Community Service activity is expected to be tempe industry players able to increase sales in order to achieve economic prosperity in the village.